Traditional Chinese Medicine nursing management for a case of cervical spondylosis (中医特色疗法治疗颈椎病1例) - ZHAO Yun (赵允); JIA Xin (贾昕); JIANG Tingjie (姜婷杰); WANG Chen (王晨); WANG Miaomiao (王苗苗) (Journal of International Translational Medicine Limited, 2021)
The combined Traditional Chinese Medicine techniques have provided characteristic solution in the treatment of cervical trauma and cervical spondylosis in a setting of Traditional Chinese Medicine nursing clinics. This paper reported the experience of combined Traditional Chinese Medicine techniques in nursing management for a case of cervical spondylosis. (中医联合技术在中医护理门诊中对颈椎外伤、颈椎病联合治疗提出特色方案。本文应用颈椎外伤、颈椎病联合中医技术, 采用多管齐下、标本兼治个案护理, 为患者提供个性化的护理, 提高患者的生活质量。)